Japanese communicative silence talks - Ngan Ling Wong (Journal of Modern Languages, 2017)
This paper begins by defining the various meanings of silence followed by its functions in diverse contexts. Examples of how silence is used positively in different situations in Japanese society will be introduced and discussed by comparing to the British society. At the same time, this paper will provide the intriguing world of silence as a tool of communication in further insight into how the respondents perceived silence and to compare whether silence are culturally specific or shared universally by both cultures.